Branding and Digital Promotion to Increase Kub Ziae's Competitiveness in the Sembalun Tourism Area - Ondi Asroni; Angga Radlisa Samsudin; Dading Oktaviadi Resmiranta; Muhammad Innuddin; Naufal Hanif; Muhammad Tahir (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
KUB ZIAE Sembalun Bumbung is a souvenir center located on the main tourist route of Sembalun, offering products such as black garlic, organic red rice, Rinjani coffee, and dried beans. However, this business faces challenges including weak brand identity, low visibility, and the absence of digital presence. Limited digital literacy among managers also results in reliance on conventional promotion methods. This community service program aimed to enhance KUB ZIAE’s competitiveness through two key strategies: (1) strengthening offline visual identity with signboards, banners, and product labels; and (2) developing digital assets such as Google Business Profile, Instagram, and Facebook accounts, along with content creation training. A participatory approach was applied, including needs assessment, co-design, intensive training, and on-site mentoring. The results showed improved business visibility with the installation of signboards and banners, while new product labels increased consumer trust. On the digital side, the Google Business account successfully appeared in search results, Instagram posts reached hundreds of accounts, and members gained skills in creating and managing promotional content. Although challenges remain, such as limited digital literacy and internet connectivity, the intervention effectively enhanced visibility, expanded market reach, and strengthened KUB ZIAE’s image as a leading souvenir center in the Rinjani tourism area